(untitled) - Bahá'u'lláh (Wilmette, Ill., 1978)
Contents: The valley of search; The valley of love; The valley of knowledge; The valley of contentment; The valley of wonderment; The valley of true poverty and absolute nothingghess...
Keywords: Bahai Faith,Đức tin Bahai; Doctrines,Học thuyết